OPTIMIZATION OF MARKETING MANAGEMENT APPLICATION BASED ENTERPRISES OPERATIONS RESEARCH METHODS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The implementation of one of the possible approaches to the formation of the marketing strategy of a communication enterprise, based on the use of operations research methods and allowing to optimize the choice of assortment, supply volumes, market segments and prices for communication services, is considered. The results of solving the problem of nonlinear partial-integer programming using the proposed heuristic method based on iterative increase in prices for communication services and solving the problem of linear partial-integer programming using the Land and Doig method are presented.